Intentions for postsecondary education: meaning in life, school connectedness, and substance use - Fitch-Martin, Arissa R., author; Dik, Bryan, advisor; Steger, Michael, advisor; Henry, Kimberly, committee member; Youngblade, Lise, committee member (Colorado State University. Libraries, 2013)
Attempts to understand what drives some youth to continue their education after high school have mostly been unsuccessful. Persisting education past high school requires sustained commitment and planning, which are theoretically important functions of the psychological construct of meaning in life. Research often has ignored the role that meaning in life plays in educational attainment and thus may be missing an important variable. Youth who report having meaning in their lives have higher well-being, are more resilient, and are more likely to report long-term achievement oriented goals. The current study investigated the relationship between meaning, school connectedness and substance use in order to create a model to better explain college aspirations 12th graders. Participants were seniors in high school and took part in the nationally representative Monitoring the Future project. Structural equation modeling was used to assess the hypothesized model. Results demonstrated that school connectedness and parental education are significant indicators of intentions for postsecondary education. Although not directly related to academic intentions, meaning in life had strong ties to school connectedness and parental education. The current study provides evidence that meaning in life may be an important factor in academic success and persistence. Implications for interventions and future research are discussed.
Keywords: academic aspirations; school connectedness; meaning in life; adolescents